Sustainability in Agroecological Family Agriculture: Castilla Blackberry in Sumapaz - Fonseca- Carreño, Nelson Enrique (Universidad Francisco de Paula Santander, 2019)
Family farming generates employment, economic growth, development and competitiveness, aimed at enhancing competitive advantages through productive alliances, production alternatives and market specialization. There are numerous challenges facing the mulberry (rubus glaucus) value chain in Sumapaz, which must focus its efforts on closing gaps. This proposal evaluates sustainability and generates alternatives for associativity and marketing. The primary links do not apply an adequate use of agricultural and business practices to face changes in the processes of market globalization and the adoption of new forms of business development.